Analysis on mortality and disease burden of stroke in Tianjin in 1990 and 2015 - Ming-fa LIU; Mai-geng ZHOU; Shi-wei LIU; Xin-ying ZENG; Hui ZHANG; Zhong-liang XU; De-zheng WANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2018)
Objective To analyze the changes of mortality and disease burden of stroke in 1990 and 2015 in Tianjin. Methods The results of the Global Burden of Diseases Study 2015 (GBD 2015) for Chinese estimated by province were used to describe the disease burden of stroke in Tianjin. The analysis index included number of death, mortality rate, disability adjusted life year (DALY), years of life lost (YLL) and years lost due of disability (YLD). The change from 1990 to 2015 for all indexes was used to describe the transitions of disease burden of stroke in the past 25 years in Tianjin. Results In 2015, the mortality rate of stroke reached 101.53 per 100 000 people and the age-standardized mortality rate was 117.73 per 100 000 people. The DALY, YLL, and YLD reached 285 558.36, 265 627.77 and 19 930.60 person year, respectively, and the age - standardized DALY rate, YLL rate and YLD rate were 1870.55, 1746.63 and 123.92 per 100 000 people. Compared with the result in 1990, the number of death, DALY, YLL and YLD in 2015 were increased by 26.24%, 9.05%, 5.48% and 98.63%, respectively, while the age-standardized mortality rate, DALY rate, YLL rate and YLD rate in 2015 were decreased by 46.75%, 52.81%, 54.32% and 11.20%, respectively. In different types of stroke, DALY and YLL of hemorrhagic stroke were higher, while YLD was lower than ischemic stroke in 1990 and 2015. Compared with 1990, DALY was decreased by 11.77%, YLL was decreased by 14.75%, and YLD was increased by 96.87% in hemorrhagic stroke in 2015, while DALY was increased by 47.38%, YLL was increased by 44.04% and YLD was increased by 100.08% in ischemic stroke in 2015. Conclusions Disease burden of stroke became more and more serious in Tianjin, of which the ischemic stroke was most serious, and the disease burden of stroke in men was greater than that in women.